Satellite Account of Household Production. Methodological Remarks and Results for Poland - Ilona Błaszczak-Przybycińska; Marta Marszałek (Ekonometria)
The household production is a big aggregate which has no reflection in the current European system of national accounts. The market value of that production accounts for less than 10- 15% of the total household production. Generally, household production can be estimated using the input method. Unpaid household work is the main input. There were many proposals of the way of estimating household work, but most economists prefer the market cost method. The first full sequence of accounts, entitled the Household Production Satellite Account for Poland (HHSA) was developed for 2011. It was proven that the value of the household work constitutes approximately 80% of the total value of household production, while the total value of household production in relation to GDP amounted to approximately 36.5%. Providing the regular calculation of the HHSA, which is a supporting tool for the core national accounts, will allow the recognition and better understanding of the transfers and interactions between the market and households. The value and size of the goods and services produced by households can be compared with similar products produced on the market by enterprises.(original abstract)